Granulated Faith-Holding: Examples from the Vocation of Science (Max Weber, Edward Shils, David Martin). (13th August 2015) - Keenan, William
Abstract : The contention here is that however firmly faiths are formally promulgated in creeds and public declarations, there exist innumerable "granulated" ways in which they are 'held' by groups and individuals. There is little published research work on granulated faith-holding, particularly on informal and implicit calibrations of shared and multi-faith frameworks of conviction and commitment in relation to the structuration of faith traditions. Building on the work of Bailey, Schnell and Francis, in particular, the concept of "traditioning" is introduced to address the missing "historical" dimension to theorizing in this field. Three ideal-typical modes of granulated faith-holding are constructed: monist, dualist and pluralist, and explored in the context of the critical rational Wertfreiheit vocational scientific tradition. Key biographies of three major contributors to the sociological study of religion, culture and society—Max Weber, Edward Shils and David Martin—are employed as source materials for three contrasting cameos of granulated scientific vocational faith-holding. As granulated faith-holding is likely to be evident within other domains of culture and society, such as, for example, religion, politics, intimate relations, and "fanships" in sport, élite and popular culture, the article concludes with some general lines of application of the theoretical framework formulated here.